Fremanezumab and Non-High-Dose Galcanezumab for Comorbid Cluster Headache in Patients with Migraine: Three Cases - Kenta Kashiwagi; Masahito Katsuki; Shin Kawamura; Senju Tachikawa; Atsuko Ono; Akihito Koh (Neurology International, 2023)
A new treatment option for cluster headache (CH) prevention is needed. Monoclonal antibodies (mABs) against calcitonin gene-related peptide (CGRP) ligands are used as a preventative treatment for migraine. Considering the CGRP’s role in the CH attack’s ignition and upkeep, fremanezumab and galcanezumab have been evaluated for CH preventative treatment. However, only high-dose (300 mg) galcanezumab has been approved for episodic CH prevention. We herein report three cases of migraine and comorbid CH with previous failures of preventive treatments. Two cases were treated with fremanezumab and one with non-high-dose galcanezumab. All three cases showed good results, not only for migraine, but also for CH attacks. This report suggests the efficacy of CGRP-mABs for CH prevention. Our cases differed from cases in the phase 3 trials of CGRP-mABs for CH prevention in two ways: first, our patients had both migraine and comorbid CH, and second, we used a combination of CGRP-mABs with preventative drugs, such as verapamil and/or prednisolone, to treat CH. Future accumulation of real-world data may prove the efficacy of CGRP-mABs for CH prevention.